Peran Badan Permusyawaratan Desa (BPD) dalamPengelolaan Dana Desa(Studi Kasus di Desa Pilang Kecamatan Masaran Kabupaten Sragen) - Rahayu, Restiana Putri, Drs. Achmad Muthali'in, M. Si (2016)
The Purpose of this study is to describe the role of Village Consultative Body in fund management village in the Pilang Village District Masaran Regency Regency of Sragen constraints and solutions. This study uses kualitative approach with data collection trough interviews, observation, and documentation. Validity of the data whit the triangulation of source and collection techniques data. Analysis was performed whit a model interactive data collection, reduction, presentation, and drawing conclusions. The Subject of this studi is the head and village, cairmand and BPD member, and the community in the village Pilang district Masaran regency of Sragen. Object under investigation is the role BPD in management village fund in the village Pilang Masaran District of Sragen. The result of this study indicate that role of BPD in the village fund management is done by conveying the idea of this village fung management, supervision, and monitoring in the village fung management, evaluation, and criticized the report on fundmanagemnent headman of the village. Constrtaints faced by BPD in the management of village fund includes disbursement almost closing the year and the lack of participation by community groups at mettings auction prioritization fund management village, delay Pokmas in the submission of accountability report the result of the implementation of the fund management of the village, as well as the actual result are not in accordance whit draft plan wich has been agreed in advance. BPD solutions to overcome these obstacles is to improve cooperation between the village, the BPD, LP2MD, and community group as well as meet directly Pokmas when delivering as meeting invitation, appoint a representative from each PokMas more proficient and expert in making accountability reports, and conduct surveys directly to the field to check the implementation of the project.